(3YeOI GdMSGHs - (3YHO GdhgGH Hf EHQGgje Hf YHO GdhgGH GdNRQLj GdRfLGfj,J (B655 (3g` s ((3CejQ cdGf Hf CejQ Hf CejQ EeGe s)
(3ChdgG (B:s
(3hHYO , adeG QGjJ Cf Yde GdMSGH CLd GdYdhe GdQjGVjI hhLOJ GdeUfaGJ ajg ZjQ hGajI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B179 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B216s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B67 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs